Gestation related karyotype, QF‐PCR and CGH‐array failure rates in diagnostic amniocentesis. (30th June 2016) - Lawin O'Brien, Anna; Dall'Asta, Andrea; Tapon, Dagmar; Mann, Kathy; Ahn, Joo Wook; Ellis, Richard; Ogilvie, Caroline; Lees, Christoph
Abstract: Background: Few data exist describing laboratory related failure rates in prenatal diagnosis. The aim of this study is to assess the laboratory associated failure rate for karyotype, QF‐PCR and CGH‐array following amniocentesis in relation to gestation. Methods: Retrospective database study of amniocenteses performed 2004–2014 comparing laboratory failure rate for karyotype, QF‐PCR and CGH‐array between 16 + 0 and 40 + 0 weeks' gestation. Results: A total of 10 484 amniotic fluid test results were collected in three databases. Karyotype failed in 41/1797 (2.3%) tests; failure rate was significantly greater with advancing gestation reaching 43% at 36–40 weeks. QF‐PCR failed in 132/5715 tests (2.3%) and was significantly greater with advancing gestation reaching 7% at 36–40 weeks. For CGH‐array, 10/298 tests (3.4%) failed analysis. In one case, no result was obtainable by any technique. Conclusions: These data provide gestation specific laboratory failure rates for amniocentesis enabling informed decisions about the timing and laboratory technique most applicable to the clinical situation. Before 20 weeks, karyotype is least likely to fail of the three techniques. However, in the late third trimester, QF‐PCR and, in particular, karyotyping are more likely to fail than CGH‐array. Although there is some overlap between the three different tests, they may be preferentially offered in different clinical scenarios. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known about this Topic? Karyotype failure following third trimester amniocentesis increases with advancing gestation. Few data exist comparing the gestation laboratory failure rates from QAF‐PCR, CGH‐array and karyotype. What does this Study Add? Karyotype, CGH array and QF‐PCR overall have similar laboratory failure rates. The laboratory failure rates for QF‐PCR and karyotype but not CGH‐array increase with gestation, with karyotype being unreliable in the third trimester.